Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1161/strokeaha.114.005170
|View full text |Cite
|
Sign up to set email alerts
|

Features Predictive of Brain Arteriovenous Malformation Hemorrhage

Abstract: Background and Purpose-Although there is generally thought to be a 2% to 4% per annum rupture risk for brain arteriovenous malformations (bAVMs), there is no way to estimate risk for an individual patient. Methods-In this retrospective study, patients were eligible who had nidiform bAVMs and underwent detailed pretreatment diagnostic cerebral angiography at our medical center from 1996 to 2006. All patients had superselective microcatheter angiography, and films were reviewed for the purpose of this project. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 35 publications
0
28
0
2
Order By: Relevance
“…29 In our series, the mean age of patients with hemorrhage was significantly lower than that of those without hemorrhage ( Figure 2). However, in the study led by Sahlein et al, 30 the hemorrhage group was statistically significantly older than the nonhemorrhage group. In our series, a significantly higher hemorrhage rate (53.2%) occurred in the elderly patients (>60 years) compared with the rate in patients 40e59 years old ( Figure 1).…”
Section: Patient Age and Initial Presentationmentioning
confidence: 86%
“…29 In our series, the mean age of patients with hemorrhage was significantly lower than that of those without hemorrhage ( Figure 2). However, in the study led by Sahlein et al, 30 the hemorrhage group was statistically significantly older than the nonhemorrhage group. In our series, a significantly higher hemorrhage rate (53.2%) occurred in the elderly patients (>60 years) compared with the rate in patients 40e59 years old ( Figure 1).…”
Section: Patient Age and Initial Presentationmentioning
confidence: 86%
“…Fok et al., Tong et al . and Sahlein et al . showed that small size was a risk factor for hemorrhagic presentation.…”
Section: Discussionmentioning
confidence: 98%
“…). For instance, HHT‐1 exhibits mutations in endoglin (ENG), which codes for an accessory protein of the TGF‐β adaptor complex (Gross et al, ; Goyal et al, ; Sahlein et al, ; Ieva et al, ), whereas HHT‐2 presents with mutations in activin‐like kinase 1 (ALK‐1), which codes for a transmembrane‐bound kinase receptor associated with the transmission signature of TGF‐β (Gross et al, ; Goyal et al, ; Sahlein et al, ; Ieva et al, ). TGF‐β is a cytokine regulating critical developmental milestones such as cell differentiation, migration, adhesion and proliferation.…”
Section: Pathogenesis and System Geneticsmentioning
confidence: 99%